2021
DOI: 10.1523/jneurosci.1321-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Dopamine Neurons Represent Reward Differently during Action and State Guided Learning

Abstract: Neuronal underpinning of learning cause-and-effect associations in the adolescent brain remains poorly understood. Two fundamental forms of associative learning are Pavlovian (classical) conditioning, where a stimulus is followed by an outcome, and operant (instrumental) conditioning, where outcome is contingent on action execution. Both forms of learning, when associated with a rewarding outcome, rely on midbrain dopamine neurons in the ventral tegmental area (VTA) and substantia nigra (SN). We find that, in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 76 publications
0
5
1
Order By: Relevance
“…Premature actions may result from an inability to learn the task contingency or a failure to inhibit a response, despite knowledge that inappropriate responding will not be rewarded. Thus, while our previous work had not shown any associative learning deficits in adolescents 68 , we cannot rule out that learning deficits in adolescents may have contributed to some of the observed behavioral age differences.…”
Section: Discussioncontrasting
confidence: 65%
“…Premature actions may result from an inability to learn the task contingency or a failure to inhibit a response, despite knowledge that inappropriate responding will not be rewarded. Thus, while our previous work had not shown any associative learning deficits in adolescents 68 , we cannot rule out that learning deficits in adolescents may have contributed to some of the observed behavioral age differences.…”
Section: Discussioncontrasting
confidence: 65%
“…In vivo and ex vivo recordings have revealed that VTA dopamine neurons in rats have higher tonic firing rates during adolescence compared to adulthood, peaking during late adolescence (PND40-50). In addition, although adolescent rats have a similar proportion of phasic activity episodes, these are consistently longer compared to those of adults (McCutcheon and Marinelli, 2009 ; McCutcheon et al, 2012 ; Marinelli and McCutcheon, 2014 ; but see Kim et al, 2016 ; McCane et al, 2021 ). It is currently unknown whether these age-related changes are specific to different defined neuronal populations or pathways.…”
Section: The Mesocortical Dopamine Pathway: a Uniquely Late Maturing ...mentioning
confidence: 99%
“…This may be related to changes in CB1 levels on prefrontal glutamatergic terminals in the VTA controlling the activity of dopamine neurons (Carr and Sesack, 2000 ; Heidbreder and Groenewegen, 2003 ; Gabbott et al, 2005 ; Beier et al, 2015 ). These complex changes may represent an important mechanism underlying developmental changes in VTA responses to rewarding and aversive environmental stimuli (Kim et al, 2016 ; McCane et al, 2021 ) and dopamine-related behaviors (Spear, 2000 ).…”
Section: Dopamine and Endocannabinoid Modulation Of Prefrontal Circui...mentioning
confidence: 99%
“…One of the ambitions of biologically inspired neural coding in models for robot control is to characterize and provide a plausible brain model for the behavioral neuroscience of reinforcement and extinction [12,13].…”
Section: Reinforcement and Extinctionmentioning
confidence: 99%